The New ACSM Recommendations for Preventing Cardiovascular Events at Fitness Facilities. (November 2020) - Riebe, Deborah; Baggish, Aaron L.; Franklin, Barry A.; Jaworski, Carrie A.; Thompson, Paul D.
Abstract : Apply It!: This article will help readers to: understand the cardiovascular risks associated with physical activity and learn more about the steps that exercise professionals can take to promote safety in health fitness facilities.